2011
DOI: 10.1371/journal.pone.0026092
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Specification and Immune Response Transcriptional Signatures of Pericardial and Subcutaneous Adipose Tissue

Abstract: Cardiovascular disease (CVD) remains the leading cause of morbidity and mortality in the United States. Recent studies suggest that pericardial adipose tissue (PCAT) secretes inflammatory factors that contribute to the development of CVD. To better characterize the role of PCAT in the pathogenesis of disease, we performed a large-scale unbiased analysis of the transcriptional differences between PCAT and subcutaneous adipose tissue, analysing 53 microarrays across 19 individuals. As it was unknown whether PCAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…This difference coincides with a divergence in the expression of genes associated with glucose intolerance (increased Glut4 , decreased insulin receptor (Lefebvre et al, 1998)) and atherosclerosis (increased CCL4 , CCL5 , and IL-1β ) (Lau et al, 2011). Unexpectedly, we have also observed differences in gene expression across a WAT depot.…”
Section: Technical Aspectsmentioning
confidence: 89%
See 2 more Smart Citations
“…This difference coincides with a divergence in the expression of genes associated with glucose intolerance (increased Glut4 , decreased insulin receptor (Lefebvre et al, 1998)) and atherosclerosis (increased CCL4 , CCL5 , and IL-1β ) (Lau et al, 2011). Unexpectedly, we have also observed differences in gene expression across a WAT depot.…”
Section: Technical Aspectsmentioning
confidence: 89%
“…As was mentioned above, significant differences exist between the expression profile of adipocyte genes between tissues and within tissues (Brochu et al, 2001; Fujimoto et al, 1999; Kloting et al, 2010; Lau et al, 2011; Lefebvre et al, 1998; Nicklas et al, 2004). Analysis of adipocyte size using our described method has indicated that there are differences in the distribution of adipocyte sizes and average area between inguinal and epididymal WAT (Fig.…”
Section: Technical Aspectsmentioning
confidence: 96%
See 1 more Smart Citation
“…Table 2 provides an overview of developmental genes that are differentially expressed among adipose tissue depots in rodents and humans. Most notably, in humans, a set of homeobox-type transcription factors was identified to be differentially regulated between SAT and VAT (HOXC9, HOXC10, HOXA9, HOXA10, HOXC6, HOXB7 and PAX3) (Brune et al, 2016;Lau et al, 2011;Vohl et al, 2004), as well as between different SAT depots. HOXA2, HOXA3, HOXA4, HOXA5, HOXA9, HOXB7, HOXB8, HOXC8 and IRX2 are downregulated in both adipocytes and stromal vascular cells of the gluteal subcutaneous compared with the abdominal subcutaneous depot.…”
Section: Expression Of Developmental Genes Differs Between Adipose Timentioning
confidence: 99%
“…16 In addition, the transcriptome of PAT from patients with CAD revealed an upregulation of genes involved in immune and inflammatory processes. 14,17 Exercise training has shown numerous beneficial effects on adipose tissue health in rodents 18 and humans. 19 In well-conditioned athletes, the mass of adipose tissue accounts for 2% to 3% of body weight, suggesting the beneficial role of exercise in reducing fat mass.…”
Section: Introductionmentioning
confidence: 99%